ANALYSIS OF FACTORS AFFECTING DIVIDEND POLICY WITH GOOD CORPORATE GOVERNANCE AS INTERVENING VARIABLES IN SERVICES COMPANIES IN INDONESIA STOCK EXCHANGE - Zulkarnen, Zuliana (Asosiasi Dosen Akuntansi Indonesia, 2018)
The purpose of this study was to determine and analyze the effect of liquidity ratio (CR), leverage (DER), profatibilitas (ROA), asset growth (AG), retun on equity (ROE) the dividend policy simultaneously and partially as well as to identify and analyze the effect of CR, DER, ROA, AG, ROE on dividend policy with good corporate governance as an intervening variable. The population in this study is the service companies listed in Indonesia Stock Exchange during the period 2012-2015. The total sample in this study as many as 10 companies for 4 years in a row so that the total observation is as much as 40. The results of this study prove that CR, DER, ROA, AG, and ROE significant influence simultaneously and partially AG positive and significant impact on policy dividends, and CR, DER, ROA, ROE is negative and significant effect on dividend policy. Based on the analysis path, good corporate governance variables were able to mediate the relationship between DER and ROA on dividend policy of good corporate governance while not being able to mediate the relationship between CR, AG, and ROE on dividend policy.